Removal of Iron and Copper Ions from Water Using Cashew Nut Shell Adsorbent: Langmuir, Freundlich, Redlich-Peterson and Harkin-Jura Isotherms - Kefas, Haruna Mavakumba; Luka, Yusufu; ABUBAKAR, ABDULHALIM MUSA; Egbeji, Augustine Odey (Indochina Applied Sciences, 2025)
Elevated copper (Cu) and iron (Fe) levels can pose a threat to biodiversity. Removal of those metallic impurities was achieved in this study using cashew nut shell (CNS) adsorbent. Greater sorption of 87.40% Cu and 99.50% Fe occurred at 10 min contact time and 0.40 g CNS dosage. This study also targets the determination of the adsorption mechanism of the process, where it was discovered that it satisfied a favorable monolayer adsorption on homogeneous active sites at 1.1106 mg g –1 Cu and 1.0995 mg g –1 Fe uptakes (q_e), described by the Langmuir isotherm with R2 value > 0.9990. The run essentially carried out using Lake Gerio water sample in Nigeria also satisfy the Redlich-Peterson model whose constant exponent, β = 0.9773 for Cu and 0.9985 for Fe ≅ 1, implied similar behavior with Langmuir isotherm assumption at specific temperature of 30°C. Effect of varying contact time and CNS dosage was also tested on % equilibrium sorption and q_e. Both Harkin-Jura and Freundlich equations poorly fit the empirical result with no match to adsorption evidence depicted after Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM) and Atomic Absorption Spectroscopy (AAS) analysis carried out. Removal of heavy metals such as Cu and Fe from lakes and rivers will contribute to benthic organisms and sediment quality, food chain integrity, fish and seafood safety, recreational use, human and environmental health. Thus, the potentials demonstrated by CNS in the removal of Cu and Fe in this study as well as other heavy metals already investigated, will ensure long-term ecosystem resilience.